Peran Guru Pendidikan Agama Islam (PAI) dalam Meningkatkan Kecerdasan Spiritual dan Pembentukan Karakter Islami Siswa di SMKN 1 Leuwiliang Bogor - Latipatinupus, Latipatinupus; Riyanto, Riyanto; Srihartini, Yusi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Reality shows that the increase in spiritual intelligence and the formation of Islamic character still faces various obstacles such as the decline of positive values carried out by students at school, the violation of school rules committed by students, the reduction of student manners towards teachers and the limitation of interaction and attention of PAI teachers to students because of the large number of students and the time they have is very limited. The objectives of this research are to; 1). Knowing the role of PAI teachers in improving spiritual intelligence and the formation of students' Islamic character at SMKN 1 Leuwiliang, 2). Identifying the challenges faced by PAI teachers in improving spiritual intelligence and the formation of Islamic character at SMKN 1 Leuwiliang at SMKN 1 Leuwiliang, 3). To find out the extent of the success of PAI teachers in achieving the goals of Islamic religious education in the context of spiritual intelligence and character formation at SMKN 1 Leuwiliang. The research method used is field qualitative with research instruments, namely: observation, interviews and documentation. The results of the study are: 1). The role of PAI teachers in improving spiritual intelligence and the formation of students' Islamic character at SMKN 1 Leuwiliang is good with indicators that the role of PAI teachers is not only as a transfer of knowledge but also has other roles such as facilitating worship practices, increasing spiritual intelligence, providing moral guidance, being an exemplary example, 2). The challenges faced by PAI teachers in improving spiritual intelligence and the formation of Islamic character of students at SMKN 1 Leuwiliang are that the competence of PAI teachers must be developed by participating in trainings both independently at PMM and facilitated by schools. Another challenge is the lack of awareness of students in studying Islam, the variety of student backgrounds that affect the understanding of religious values. 3). PAI teachers at SMKN 1 Leuwiliang have succeeded in improving spiritual intelligence and forming Islamic character with success indicators, namely the large number of student participation involved in religious activities held at school.